2012
DOI: 10.1111/j.1751-7133.2011.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Initial Description of Cerebral Oximetry Measurement in Heart Failure Patients

Abstract: Cerebral oximetry is a noninvasive technology using near-infrared spectroscopy (NIRS) to monitor regional cerebral tissue oxygen saturation (SctO(2)). NIRS has been widely used for assessing cerebral tissue oxygenation in a variety of populations including the fields of neonatology, anesthesiology, neurology, and cardiac surgery.However, little information has been reported on cerebral oximetry in heart failure (HF) patients. In this observational study, we enrolled 30 patients (15 men) aged 23 to 82 years (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…43 Interestingly, a recent study using cerebral oximetry has demonstrated that cerebral tissue oxygen saturation in many heart failure patients is low, despite nearly normal levels measured in the arterial blood. 47 It seems that the same mechanism activated by brainstem hypoxia might be responsible for heightened central sympathetic tone in both heart failure and systemic arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…43 Interestingly, a recent study using cerebral oximetry has demonstrated that cerebral tissue oxygen saturation in many heart failure patients is low, despite nearly normal levels measured in the arterial blood. 47 It seems that the same mechanism activated by brainstem hypoxia might be responsible for heightened central sympathetic tone in both heart failure and systemic arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Diastolic blood pressure shows positive correlation, approximately 1-2% per 10mmHg, with cerebral oximetry in congestive heart failure. 40 It is possible that a similar relationship exists in patients without heart failure or those in the beach chair position, but this has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…27,28,29 The significance of the cerebral oximeter can be further demonstrated by substituting equation 3 (assuming blood distribution to be 70% venous (Kv = 0.7), 30% arterial (Ka = 0.3), and negligible amount in the capillaries (Kc = 0) and ERROR assumed to be zero for the ideal case as suggested by Ito et al 11 ) into equation 6 and solving the ratio of CMRO 2 to CBF as a function of S ct O 2 (equation 7). normalCnormalMnormalRO2/normalCnormalBnormalF=false(SpO2SnormalcnormaltO2false)×normalK1+normalK2

Where K1 = (1.34 × [tHb]) /0.7

And

K2 = 0.003 × (P a O 2 − P jb O 2 ).

Solving equation 7 for S ct O 2 then becomes (equation 8): SnormalcnormaltO2=SpO2+false(normalK2normalCnormalMnormalRO2/normalCnormalBnormalFfalse)/normalK1 From this equation, it can be deduced that the S ct O 2 has a proportional relationship to S p O 2 and CMRO 2 and inversely proportional with CBF.…”
Section: Discussionmentioning
confidence: 99%